Innovation of Instagram Use in Improving Business Performance of the Creative Industry in the Fashion Sub sector - Hendrayati, Heny; Atrisia, Marchela Indah; Pinasthika, Azhyra Rana; Susanto, Perengki; Juniari, Rosa Prafitri (Politeknik APP Jakarta, 2022)
This study aimed to find out an overview of the use of social media, especially Instagram in the Creative Fashion Industry in Bandung City and to determine the effect of innovative use of Instagram social media in improving business performance in the Creative Fashion Industry in the City of Bandung. The population was calculated based on the data on the number of clothing business actors registered in the SMEs assisted by the Department of Cooperatives and Small and Medium Enterprises (SMEs) in Bandung. Based on the results of simple correlation analysis, simple linear regression analysis, and hypothesis testing (T-test), it can be seen that the Social Media and Business Performance variables had a strong relationship and had a positive influence between the variables.